Bright Sources in a Chandra Survey of the Bar Region in the Small Magellanic Cloud Galaxy - Taylor, P.; Zezas, A.; McDowell, J. C.; Hatzidimitriou, D.; Kalogera, V.; Fabbiano, G. (American Astronomical Society Meeting Abstracts, 2003)
We present a study of bright X-ray sources in the central part of the Small Magellanic Cloud based on a survey performed with the Chandra X-ray Observatory (see accompanying poster by J. McDowell et al). From the 122 sources (at the 3σ level), detected within the 1280 arcmin2 covered by the survey, we concentrate on the 16 brightest sources (>100 counts; LX > 1035erg/s) for which we can perform detailed spectral and timing analysis. These sources include two known supernova remnants (in one of which we identify a weak central point-like source), seven known X-ray binaries, and five previously detected sources which are most likely pulsar binaries, based on spectra and variability from the Chandra data. Two sources were not detected by any previous scans and are new transient candidate X-ray binary pulsars. This work was supported in part by the SAO intern program under NSF grant AST-9731923 and in part by NASA Grant G02-3117X.